(untitled) (Journal of the College of Basic Education, 2025)
Adaptive learning is one of the recent approaches in the field of teaching, based on the fact that learners’ abilities are not uniform. Therefore, it is natural to pay effective attention to meeting learners’ needs by classifying them into different learning styles that provide them with knowledge based on their individual style and acceptance of the style they desire to learn. This will directly reflect on increasing their motivation, as it will take into account individual differences, potentially providing learners with equal learning opportunities against which their achievement, both in terms of skill and knowledge, can be measured. Therefore, the current research seeks to achieve the following objectives: Develop a teaching strategy based on adaptive learning to develop geometric thinking in the perspective subject among students in the Department of Art Education Measure the effect of the strategy on developing geometric thinking among students in the Department of Art Education. To achieve the research objectives, the researcher formulated several hypotheses to discuss the results. The research was limited to: The boundaries of the current research are limited to the following: Spatial boundaries: College of Fine Arts, University of Diyala. Temporal boundaries: Academic year 2023-2024 Human boundaries: Students of the Department of Art Education, second year. Objective boundaries: The geometric thinking scale prepared by the researcher, the educational content of the perspective course, and these skills include: drawing flat and three-dimensional shapes. The researcher adopted two research approaches: the descriptive and the experimental approach. The research population for the current study was students of the College of Fine Arts, and the research sample consisted of (67) male and female students. The researcher established equivalence among them on several variables. The researcher then personally studied the members of the experimental and control groups throughout the duration of the experiment. The research required the development of a tool to measure geometric thinking, and the researcher obtained validity and reliability for all research tools. The research results revealed the effectiveness of building a strategy based on adaptive learning and its impact on developing geometric thinking in the perspective course among students of the Department of Art Education. In light of the findings, the researcher developed a set of conclusions, recommendations, and proposals.